Gambaran Pola dan Derajat Luka pada Kasus Kekerasan Mekanik di RSUD Tipe B Provinsi Sulawesi Utara - Damayanti, Nadia; Siwu, James F.; Kristanto, Erwin G. (Medical Scope Journal, 2026)
Abstract: Mechanical violence is a common cause of injuries found in criminal cases in Indonesia. This study aimed to describe the wound patterns and degrees of injury in mechanical violence cases at a Type B Regional General Hospital in North Sulawesi Province during the period of July 2023 to June 2025. This was a retrospective and descriptive study. The results obtained 32 patients with a total of 54 injuries analyzed based on medical records and Visum et Repertum. Blunt-force trauma was the most frequent type (75%), followed by sharp-force injuries (18.8%). The majority of patients sustained single injuries (62.5%) with mild to moderate severity. Lacerations, contusions, and abrasions were the most common wound types, predominantly measuring 1–5 cm, with the head as the most frequent location. In conclusion, mechanical violence is dominated by blunt trauma, producing single injuries of mild to moderate severity. Variations in wound patterns are influenced by impact energy, force direction, and the interaction between perpetrator and victim. Therefore, wound pattern analysis holds significant importance for event reconstruction, legal enforcement, and violence prevention strategies. Keywords: wound pattern; injury severity; mechanical violence    Abstrak: Kekerasan mekanik merupakan penyebab luka yang sering ditemukan pada kasus kriminal di Indonesia. Penelitian ini bertujuan untuk mendapatkan pola dan derajat luka pada kasus kekerasan mekanik di RSUD Tipe B Provinsi Sulawesi Utara periode Juli 2023–Juni 2025. Jenis penelitian ialah deskriptif retrospektif. Hasil penelitian mendapatkan 32 pasien dengan 54 luka berdasarkan rekam medis dan Visum et Repertum. Kekerasan tumpul paling banyak ditemukan (75%), disusul kekerasan tajam (18,8%). Mayoritas pasien mengalami luka tunggal (62,5%) dengan derajat ringan hingga sedang. Robek, memar, dan lecet merupakan bentuk luka tersering, terutama berukuran 1–5 cm dengan kepala sebagai lokasi paling sering. Simpulan penelitian ini ialah kekerasan mekanik didominasi trauma tumpul yang menghasilkan luka tunggal berderajat ringan hingga sedang dengan variasi pola luka dipengaruhi energi benturan, arah gaya, serta interaksi pelaku dan korban. Analisis pola luka memiliki nilai penting dalam rekonstruksi kejadian, penegakan hukum, dan strategi pencegahan kekerasan. Kata kunci: pola luka; derajat luka; kekerasan mekanik